The Influence of Educational Background and Work Experience on Employee Performance at Suzuki Mobil Megahputra Sejahtera Palopo Branch - Tasik, Friskah Rante; Tonapa, Hilda Damayanti; Aprianti, Dini; Amri, Amri; Marsal, Marsal (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to determine and analyze the influence of educational background and work experience on employee performance at PT. Megahputra Sejahtera, Palopo branch. The type of research conducted is quantitative. The types of data used are derived from primary and secondary data. Data collection was carried out through observation, interviews, and questionnaires. The number of samples used was 30 employees. Data analysis used was descriptive analysis, validity testing, reliability testing, and multiple linear regression analysis. The results of the study indicate that simultaneously educational background and work experience have a significant effect on employee performance. Partially, educational background has a significant effect on employee performance at PT Megahputra Sejahtera, Palopo branch, while work experience also has a significant effect on employee performance.